Development of group B meningococcal vaccine: a progress review - Wei ZHAO; Shuang BAI; Yan-li KANG (Zhongguo gonggong weisheng, 2022)
Epidemic cerebrospinal meningitis is a respiratory infectious disease caused by Neisseria meningitidis, most commonly manifesting as meningitis and septicaemia. Due to the lack of effective prevention measures, serogroup B Neisseria meningitidis (MenB) has become one of dominant epidemic bacterial groups. In recent years, the emergence of reverse vaccinology has greatly promoted the research on serogroup B meningococcal vaccine, and researches on the vaccine have also made a breakthrough. In order to develop a more effective meningococcal vaccine, this article reviews the research progress on new protein antigen vaccine, outer membrane vesicle vaccine and recombinant protein vaccine in the field of MenB vaccine.